Hubungan Pengetahuan dan Paritas Ibu Terhadap Kunjungan Ibu Hamil Trimester III di BPM Emilia, AM.Keb Kabupaten Pali Tahun 2023 - Ratna Dewi; Intan Intan (Universitas Pahlawan Tuanku Tambusai, 2023)
AKI in Indonesia is still high, the direct causes are bleeding, infection, eclampsia, prolonged labor, and complications of miscarriage. Indirect causes are 4T late in detecting high risk pregnant women, late in making family decisions to refer, late in reaching referral facilities, and late in getting help at referral facilities. Antenatal care during pregnancy at least 4 times, services include anamnesis and monitoring of the mother and fetus to assess normal progress. Factors that influence the visit of pregnant women are economic factors, education, family support, parity, age, knowledge, and geography. The aim of the study was to determine the relationship between mother's knowledge and parity towards third trimester pregnancy visits at BPM Emilia, AM.Keb, Pali District. The study used an analytic survey method with a cross sectional approach. The population in the study were all pregnant women who checked their pregnancies at BPM Emilia, AM.Keb, Pali district. The accidental sampling technique consisted of 30 respondents. The results of the study were 20 pregnant women who visited ≥ 4 antenatal care visits (66.7%) more than 10 respondents who had <4 pregnancy visits (33%), 26 pregnant women who had good knowledge (86.7%), more than pregnant women who had less knowledge, 4 people (13.3%), and pregnant women with high parity, 7 people (23%), less than pregnant women with low parity, totaling 23 people ( 76.3 %). The results of the Chi-Square test showed that there was no significant relationship between knowledge of visits to pregnant women where the value of p_value = 0.095 > α (0.05) and the results of the Chi-Square test showed that there was no significant relationship between parity and visits of pregnant women where the value of p_value = 0.571 > α (0.05). It is hoped that midwives can provide health education to pregnant women about the importance of prenatal checks to detect complications and have a safe pregnancy. Keywords: Knowledge, parity, visits of pregnant women